2018
DOI: 10.31298/sl.142.1-2.2
|View full text |Cite
|
Sign up to set email alerts
|

Raznolikost i strukturiranost hrvatskih kontinentalnih i alpsko-dinarskih populacija bijele johe (Alnus incana /L./ Moench subsp. incana); geografska i okolišna izolacija kao uzrok fenotipske divergencije

Abstract: UDK 630* 181.8 + 164 (001) Izvorni znanstveni članci -Original scientific papers Šumarski list, 1-2 (2018): 19-32

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…This suggests that, at least to some degree, it is genetically determined for Quercus variabilis Blume. In Alnus species, NV displays less variability at the intrapopulation level and more variability at the interpopulation level with respect to other traits (e.g., leaf length, leaf width, leaf area, perimeter and petiole length) [19,38]. Given these observations and the results from this study, NV appears to be a more conservative trait than leaf shape.…”
Section: Inter-and Intrapopulation Variability In Leaf Traitssupporting
confidence: 56%
See 3 more Smart Citations
“…This suggests that, at least to some degree, it is genetically determined for Quercus variabilis Blume. In Alnus species, NV displays less variability at the intrapopulation level and more variability at the interpopulation level with respect to other traits (e.g., leaf length, leaf width, leaf area, perimeter and petiole length) [19,38]. Given these observations and the results from this study, NV appears to be a more conservative trait than leaf shape.…”
Section: Inter-and Intrapopulation Variability In Leaf Traitssupporting
confidence: 56%
“…Considering various leaf morphological traits, hybrids between black and grey alder overlap with one or both parents or hold an intermediate position and appear to be closer to A. incana [14,16,18]. Multivariate analysis of leaf morphological traits has shown that hybrids have an intermediate position and are closer to A. incana [14,15,19,20]. It was reported by [39] that the germination of a hybrid seed was only successful when A. incana For A. rohlenae, a weak positive correlation between NV and CS was determined in the population PK (R 2 = 0.113, p < 0.05).…”
Section: Hybrids In Studied Populationsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this may be due to the recent recognition of the environment's role in shaping spatial patterns of gene flow and genetic variation [109][110][111]. Nowadays, IBE is known as a widespread but complex phenomenon in nature [98,112], driving genotypic and phenotypic divergence in several taxa, including tree species like Fraxinus angustifolia Vahl [113], Alnus incana (L.) Moench [114], Populus nigra L. [115], and Sequoiadendron giganteum (Lindl.) J.Buchholz [116].…”
Section: Influence Of the Environment And Human Activities As Modulators Of Ilex Guayusa Population Structurementioning
confidence: 99%